Knowledge, attitude and practice toward family planning among married men in Hospital Universiti Sains Malaysia - Siddik, Nur Aqilah Abu Bakar (2020)
Family planning is important for a family institution. Family planning can be a disharmony to the family if they take things too easily. The objectives of this study were to determine knowledge, attitude and practice towards family planning among married men in Hospital Universiti Sains Malaysia (HUSM). A cross- sectional design study was undertaken involving 90 respondents that were recruited using non-probability convenience sampling in pharmacy, HUSM. The data collection period was from February 2020 until March 2020. A self-administered questionnaire was used to collect the data. The data were then analyzed using software (SPSS) version 24.0. Only 44.4% of married men have good knowledge about FP which is considered moderate. However, the attitude and practice of FP among married men is 60% good attitude and 73.3% have poor practice respectively. Therefore, we can see that married men have a good attitude but poor knowledge and practice when it comes to family planning. The Chi -square test used to examine the association between selected socio-demographic characteristics and it was found that there is a significant association between prevalence rate on family planning and education level (p<0.044) among married men. In conclusion, this study showed that knowledge and attitude toward family planning among married men was not adequate. However, each man who is married need more interactive health education to enhance their knowledge, attitude and practice.